Effects of Irrigation Interval, Nitrogen and Phosphorus on Grain Yield and biomass of Wheat - M. Musa, Lubna; M. Abd Elmalik, Eltayeb; E. Hamad, Muawia; A. Salih, Ahmed (Gezira Journal of Agricultural Science; Vol 3 No 1 (2005), 2021)
This study was conducted for two successive seasons of 1998/1999 and 1999/2000, at the Gezira Research Station Farm, Agricultural Research Corporation, Sudan, to investigate the effects of irrigation interval, nitrogen and phosphorus levels on wheat ( Triticum aestivum L .( yield and yield components. The study consisted of three irrigation intervals (7,14,21 days), three N levels (0, 43 and 86 kg N/ha) and two P levels (0 and 43 kg P 2 0 5 /ha). Treatments were arranged in a split-split plot design with three replications. Results showed that the irrigation intervals of 7 and 14 days had positive effects on wheat grain and total dry matter yield as compared to the 21 days irrigation interval which negatively affected these parameters. Plants of the latter treatment were dwarf with thin stems and matured earlier resulting in low grain and biomass yields. The study, also, showed that the highest wheat yield was obtained with the application of N and P at the rates of 86 kg N and 43 kg P2O 5 /ha, respectively, with the irrigation interval of 7 days.